C-reactive protein does not opsonize early apoptotic human neutrophils, but binds only membrane-permeable late apoptotic cells and has no effect on their phagocytosis by macrophages - MacCall Shonna M; Alexander Karen M; Hart Simon P; Dransfield Ian (BMC, 2005)
Abstract Background It has been reported that C-reactive protein (CRP) binds both leukocyte FcγRIIA (CD32) and the plasma membrane of apoptotic cells. Since FcγRIIA becomes functionally enabled during neutrophil apoptosis, we sought to determine whether CRP bound to apoptotic neutrophils via FcγRIIA. Methods We prepared directly labelled CRP and demonstrated that it was essentially free of IgG. We looked for evidence of CRP binding to intact, membrane impermeable apoptotic human neutrophils and to FcγRIIA-transfected Jurkat cells. We examined the functional consequences of incubation with CRP upon phagocytosis of apoptotic cells by human monocyte-derived macrophages. Results We could not detect binding of purified soluble CRP to classical early apoptotic human neutrophils or to FcγRIIA-transfected Jurkat cells. In contrast, membrane-permeable late apoptotic neutrophils exhibited strong CRP binding, which comprised both Ca2+-dependent and heparin-inhibitable Ca2+-independent components. However, there was no effect of CRP binding upon phagocytosis of late apoptotic neutrophils by macrophages. Conclusion Potential apoptotic cell opsonins such as CRP may bind only to intracellular structures in cells with leaky membranes that have progressed to a late stage of apoptosis.